Clinical, hematological and histopathological aspects of experimental induction of laminitis in cattle through lipopolysaccharide infusion - Barbosa,Antônio Amaral (2020)
ABSTRACT: The purpose of this research was to confirm the changes occurring in the foot system of the heifers challenged with lipopolysaccharides (LPS), at the clinical, serum and histological levels. We studied 16 clinically healthy heifers, 14 months of age, placed in a confinement system. All the animals were provided with an accelerometer collar to establish their activity. They were categorized into two groups: the LPS group (n=8), or those which were administered two intravenous applications of 2 mL containing 0.5 μg/kg of body weight of LPS, with a 24-hour interval and the Control group (n=8) which were given two infusions of 2 mL of saline solution in the same time interval. General clinical examination and blood collection were done at 0, 4 and 8 hours post the LPS challenges and analyses of the hemograms and paroxonese-1 were performed. The animals were then slaughtered on day 4 and the laminar tissue was collected for histological analysis. The LPS group revealed a lower total leukocyte count with heart rate and greater activity. None of the animals revealed any abnormal signs symptomatic of foot pathology after histological analysis. Hence, the challenge with LPS failed to induce any clinical and histological changes in the foot tissue compatible with laminitis.